Al Qaeda's Organizational Structure and its Evolution - Gunaratna, Rohan; Oreg, Aviv (Studies in conflict and terrorism, 2010)
The inner organizational structure of Al Qaeda within the expanded framework of the "Global Jihad movement" has been a subject of much debate between scholars. As will be elaborated later, the "Global Jihad movement" is composed of several elements that possess radical Islamic ideology and conduct operational activity in different regions in the world under the banner of Jihad. The dominant factor within the "Global Jihad movement" is by no doubt Al Qaeda. The purpose of this article is to focus solely on Al Qaeda and present the formal internal structure of the organization. The article argues that Al Qaeda is first and foremost, an infrastructural organization with a formal echelon, hierarchy, sub-departmental division, and duties distribution reflecting characteristics of a guerilla and terrorist organization. The article portrays the formal layout of Al Qaeda, composed of the main command apparatus, and names the different personalities who fill the more important positions within Al Qaeda's hierarchy from its days of inception until today.